The weight of beautiful - Goldschneider, Jackie (Gallery Books, 2023)
"All Jackie Goldschneider ever wanted was to be thin. As a child, she'd stand in front of the mirror, sucking in her stomach and arching her back to feel her ribs, praying to see a model-like figure looking back. As an obese teen, lonely and tormented by her weight, her doctor encouraged her to start dieting, ultimately leading to a prolonged battle with anorexia that nearly took her life. After decades of hiding her eating disorder from friends, family, and the world, Jackie is ready to expose the realities of her devastating struggle with anorexia, including the harrowing day-to-day tactics she employed to count calories and restrict meals, her struggles with fertility and pregnancy, the effects her eating disorder had on her relationships with her husband and children, and ultimately how, in a twist of fate, becoming a reality TV star saved her life"--